Genome-wide DNA methylation analysis in ankylosing spondylitis identifies HLA-B*27 dependent and independent DNA methylation changes in whole blood. (August 2019) - Coit, Patrick; Kaushik, Prashant; Caplan, Liron; Kerr, Gail S.; Walsh, Jessica A.; Dubreuil, Maureen; Reimold, Andreas; Sawalha, Amr H.
Abstract: Background and objective: Ankylosing spondylitis is a chronic inflammatory disease characterized by inflammation of the sacroiliac joints and the spine that can lead to significant pain, immobility, and disability. The etiology and pathogenesis of ankylosing spondylitis are incompletely understood, though most patients carry the HLA-B*27 allele. The objective of this study was to evaluate DNA methylation changes in ankylosing spondylitis with the goal of revealing novel mechanistic insights into this disease. Methods: Genome-wide DNA methylation analysis was performed in whole blood DNA samples using the Infinium MethylationEPIC array in patients with ankylosing spondylitis compared to age, sex, and race matched patients with osteoarthritis as a non-inflammatory disease control. We studied 24 patients with ankylosing spondylitis, including 12 patients who carry HLA-B*27 and 12 patients who are HLA-B*27 negative. DNA methylation analysis was performed with adjustment for blood cell composition in each sample. Results: We identified a total of 67 differentially methylated sites between ankylosing spondylitis patients and osteoarthritis controls. Hypermethylated genes found included GTPase-related genes, while hypomethylated genes included HCP5, which encodes a lncRNA within the MHC region, previously associated with genetic risk for psoriasis and toxic epidermal necrolysis. Carrying HLA-B*27 was associated with robust hypomethylation of HCP5, tubulin folding cofactor A ( TBCA ) and phospholipase D Family Member 6 ( PLD6 ) in ankylosing spondylitis patients. Hypomethylation within HCP5 involves a CpG site that contains a single nucleotide polymorphism in linkage disequilibrium with HLA-B*27 and that controls DNA methylation at this locus in an allele-specific manner. Conclusions: A genome-wide DNA methylation analysis in ankylosing spondylitis identified DNA methylation patterns that could provide potential novel insights into this disease. Our findings suggest that HLA-B* 27 might play a role in ankylosing spondylitis in part through inducing epigenetic dysregulation. Highlights: A genome-wide DNA methylation study in ankylosing spondylitis (AS) was performed. DNA methylation changes in peripheral blood underlie ankylosing spondylitis. HLA-B*27 is associated robust hypomethylation of HCP5, TBCA, and PLD6 in AS. HLA-B* 27 might play a pathogenic role in AS through inducing epigenetic dysregulation.